Decreased quality of life in Duchenne muscular disease patients related to functional neurological and cardiac impairment - Juříková, Lenka; Masárová, Lucia; Panovský, Roman; Pešl, Martin; Revendová, Kamila Žondra; Volný, Ondřej; Feitová, Věra; Holeček, Tomaš; Kincl, Vladimír; Danhofer, Pavlína; Voháňka, Stanislav; Haberlová, Jana; et al. (Frontiers in Neurology, 2024)
In this prospective study involving 37 Duchenne muscular dystrophy (DMD) patients aged 8-18 years and older, we examined the impact of neurological and cardiac factors on quality of life (QoL). Our findings revealed a negative correlation between upper limb movement and overall mobility, self-service, and usual activities. Ambulatory and non-ambulatory DMD patients showed significant differences in mobility-related parameters. Cardiac evaluations demonstrated associations between mitral annular plane systolic excursion (MAPSE) and mobility-related aspects. The PEDSQL 3.0 neuromuscular model questionnaire further highlighted age-related and movement-related correlations with QoL. The loss of ambulatory status and reduced upper limb movement were negatively associated with QoL, while upper limb movement positively correlated with septal MAPSE. However, no significant associations were found between MAPSE and anxiety/depression. These findings underscore the multifaceted impact of DMD on QoL and emphasize the importance of considering both neurological and cardiac factors in comprehensive patient care.